Improved Wideband Spectrum Sensing Methods for Cognitive Radio - Miar, Yasin (Université d'Ottawa / University of Ottawa, 2012)
Abstract Cognitive Radio (CR) improves the efficiency of spectrum utilization by allowing non- licensed users to utilize bands when not occupied by licensed users. In this thesis, we address several challenges currently limiting the wide use of cognitive radios. These challenges include identification of unoccupied bands, energy consumption and other technical challenges. Improved accuracy edge detection techniques are developed for CR to mitigate both noise and estimation error variance effects. Next, a reduced complexity Simplified DFT (SDFT) is proposed for use in CR. Then, a sub-Nyquist rate A to D converter is introduced to reduce energy consumption. Finally, a novel multi-resolution PSD estimation based on expectation-maximization algorithm is introduced that can obtain a more accurate PSD within a specified sensing time.
Keywords: Power Spectral Density (PSD) estimation; Simplified Discrete Fourier Transform (SDFT); Discrete Fourier Transform (DFT); Cognitive Radio (CR); Spectrum Sensing; Welch's method; Multi Resolution PSD estimation